Evaluation, awareness and use of cattle identification and traceability system in Peninsular Malaysia - Amad Bugis, Salina (2018)
Traceability of animal and animal products are tools to overcome animal and public health or food safety issues. In 2009, the Malaysian government initiated a new traceability system which included the use of radio frequency identification (RFID) tag as an animal identification (ID) and the electronic animal movement tracking system known as ePermit2 system as an initiative to control foot and mouth disease (FMD). This study was conducted to evaluate the effectiveness of the current animal identification and traceability system in the FMD control program, to determine the performance of several commercial ear tags in terms of their retention and readability, to evaluate the level of farmers and traders knowledge, attitude and practice (KAP) of traceability, to describe the inter-state movement of cattle in the FMD control program from 2010 to 2015 and to quantify the similarity of the cattle movement network from one calendar year to the next. A total of 127 cattle ID from the ePermit2 system from 11 states in Peninsular Malaysia were randomly selected and were traced to their recorded destination to see if the cattle truly arrived to the designated destination. Scoring system was developed to categorize the findings for successful or unsuccessful trace forward or trace back. To ensure that animal movement requirement for the FMD control program is fulfilled, information on the presence or absence of the selected animal ID records from FMD antibody detection (FMDL-Ab) form were collected at the Regional Veterinary Laboratory, Kota Bharu, Kelantan. The overall traceability success rate was 21.3% among cattle that were moved for breeding and slaughter in 2013. Out of 127 cattle selected and traced at the FMD Laboratory, only five cattle (3.9%) were successfully traced to their laboratory records. A field trial on 848 cattle was conducted to evaluate four types of RFID tags (Allflex, Cybortra, TSG and Ecosensa) and three types of visual tags (Allflex, Cybortra and Ecosensa) for retention and readability. After one year, Allflex and Cyborta RFID ID devices were well retained at 89.5% and 87.8%, respectively while TSG had the poorest retention at 69.1%. For visual ID device, Allflex has the highest retention at 98.3% while Ecosensa has the lowest retention at 86.8%. Among intact RFID ear tags, 45 (6.7%) failed to be read. Allflex ID device had the highest readability (98.8%), whereas TSG brand had the lowest (79.2%). The mean of survival time for RFID ID device was highest for Cybortra and lowest for TSG brand at 487 and 416 days, respectively. For visual ID devices, the survival time was highest at 515 and lowest at 478 days for Allflex and Ecosensa, respectively. In a cross sectional survey, a total of 543 farmers and traders in Peninsular Malaysia completed a questionnaire which aimed to evaluate their KAP domains of traceability. The results showed that 61% of the respondents had good knowledge on traceability. Though the percentage of the farmers and traders that had good knowledge was moderate, their attitude (53%) and practices (52%) to be traceability compliant was slightly lower. Respondents who had secondary level of education, involved in both farming and trading and had more than 20 years’ experience in cattle industry, were more likely to have good knowledge on traceability. In addition, respondents who had more than 20 years’ experience in cattle industry and practiced intensive or feedlot husbandry system were twice more likely to have good attitude towards traceability. Respondents with tertiary level of education, who reared or traded between 101 and 1000 heads of cattle and practiced semi-intensive and intensive or feedlot husbandry system were more likely to be traceability compliant. In contrast, respondents who had never attended any courses or received training in cattle farming were less likely to have positive responses in the KAP questions. Data on cattle movements registered in the ePermit2 system from 2010 to 2015 was examined using the social network analysis (SNA). A total of 24,508 movement events were recorded involving 530,064 cattle. In 2010, a large number of out-bound movements from Kelantan and Perlis was observed. However between 2013 and 2015, the pattern of cattle movement changed with Selangor showed the largest number of out-bound cattle movements, while Kelantan had the highest number of in-bound cattle movements. State of Pahang showed a consistent increased of out-bound cattle movement from 2011-2015. All districts (a total of 90 nodes) in Peninsular Malaysia were involved in the cattle movement network for the period 2010 to 2015 with the greatest number of directed links (n = 2,972) between districts occurred in 2014. This study found that the movement of cattle was associated with Hari Raya Aidil-Fitri festive celebration which occurred between July and September each year and, to a lesser extent, Hari Raya Aidil-Adha which occurred between September and November in the period of this study. Analyses showed that the Peninsular Malaysia cattle movement network had scale-free properties where small number of districts had a large number of reported movement events, while many districts had small numbers of reported movement events. Each of the social networks constructed from 2010 to 2015 were found correlated to each other. Therefore disease surveillance efforts do not need to vary from year to year as the pattern of animal movement is similar and predictable. This study has provided comprehensive information about traceability system that is practiced in Peninsular Malaysia. Matching the physical location of cattle after inter-state movements and tracing vital laboratory records was poor. Linking the two live cattle movement module systems with the laboratory system is expected to accelerate trace back or trace forward of cattle during disease incursion. Retention and readability are part of the criteria to be emphasized when choosing RFID and visual ear tag identification devices. The current RFID device brand TSG used widely in Malaysia had the poorest readability and retention and therefore is less suitable for traceability system. The KAP of local farmers and traders were modest which suggested that more efforts for structured education and training program is necessary and needed to highlight the benefits of the traceability system. States and districts with high frequencies of out-bound cattle movement are more likely to spread a disease to other parts of the country, while states and districts with high frequencies of in-bound movements are more likely to become recipients of a disease in the event of an infectious disease incursion. Thus, those districts with high in-bound and out-bound cattle movements must strengthen the existing disease control measures to ensure reduction of disease spread and outbreaks.